Critical Utopian Action Research: Methodological Inspiration for Democratization?. Issue 2 (August 2020) - Egmose, Jonas; Gleerup, Janne; Nielsen, Birger S.
This paper provides an introduction to Critical Utopian Action Research (CUAR) as a methodology with a strong emphasis on combining critical analysis, imaginative thinking, and everyday life-based actions toward societal democratization. First, we situate CUAR in the light of current societal frameworks asking: Why the need for CUAR? We then briefly mark theoretical sources of inspiration before focusing on the Future Creating Workshop as a way to elicit what CUAR is from a methodological point of view. We exemplify how the workshop functions before we finally discuss what kind of contributions CUAR might enable in the context of local communities, workplaces, organizations, and broader societal settings.